Antecedents of career advancement of employees living with human immunodeficiency virus - Hamdi, Mohamad Halim Asyraf; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2021)
This study aims to examine factors influencing career advancement among people living with human immunodeficiency virus (PLHIV) working in Klang Valley, Malaysia, Supported by Social Equity Theory. This study has been conducted based on correlational research design. A total of 71 respondents which are PLHIV employees participated in this study using snowballing sampling technique. IBM SPSS Version 23.0 has been used to analyse data of the study. Correlation results indicated that quality of work-life has a significant and high relationship with career advancement of PLHIV. These findings further supported by regression analysis. Results of the study provide an insightful evidence on the relationship between organizations’ HIV friendly policy, quality of work life and career advancement of PLHIV employees particularly to researchers, human resource practitioners and policy makers. This article presents an agenda for future research on organizational responses to employees with HIV.